Analisis Kehilangan Hasil Panen Padi Menggunakan Combine Harvester Kubota Dc 70 Plus Di Desa Tuyat Kecamatan Lolak Kabupaten Bolaang Mongondow - Aneke Sikome; Daniel P. Ludong; Lady C. Ch. E. Lengkey (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2023)
This study aims to examine the loss of rice yields using the Combine Harvester kubota DC 70 plus machine. Yield losses in question are scattered during harvesting, left in the machine, not harvested and left behind during threshing. This research was carried out in September – October 2022 in Tuyat Village, Lolak District, Bolaang Mongondow Regency, North Sulawesi Province. Harvesting is carried out using a Kubota DC 70 plus Combine Harvester machine on Mekongga variety rice plants that are ready to harvest. The research was carried out using experimental methods. Data collection after the rice is harvested. The experiment was carried out 3 repetitions. The results showed that the average loss scattered during harvesting was (4.7 ± 1.26)%, the average loss was not harvested (0.018 ± 0.006)%, the average loss left behind on the machine was (0.18 ± 0.040)%, the average loss during threshing (0.010±0.0004)%. The total yield loss during the rice harvesting process on a 40m x 15 m land area using the Kubota DC 70 plus Combine Harvester was (4.9±1.31)%. Keywords: Combine Harvester; Loss, Paddy.